Feedback on reflection: comparing rating-scale and forced-choice formats for measuring and facilitating teacher team reflective practice. Issue 3 (3rd May 2016) - Murphy, Daniel L.; Ermeling, Bradley A.
Abstract: This study focused on elements of measurement and feedback for teacher reflective practice. The measurement component examined the use of the Survey of Reflective Practice: A Tool for Assessing Development as a Reflective Practitioner to measure reflective practice and promote reflection, and compared educator responses using rating-scale and forced-choice item formats. The feedback component observed teachers and mentors collaborating to set goals that facilitate growth as a reflective practitioner. Results suggest the instrument can be used to measure and facilitate a teacher team's level of reflection with one important caveat: our results indicate that there may be a threshold level of reflection necessary before teachers can benefit from the examined collaborative process. In addition, results suggest that the forced-choice item format might help mentors move away from a judging and evaluating mindset to a mindset of thoughtful analysis of the conditions and qualities that most accurately describe the team's reflective behavior.